Middle Ear Diseases Advances in Diagnosis and Management - Mansour, Salah (Springer International Publishing, 2018)
This book covers the latest advances in disciplines related to the middle ear pathologies such as: the innovations in the understanding of its functional anatomy and their implications along with the breakthroughs in the physiopathology of its diseases and the most recent concepts of their pathogenesis. More adapted audiological investigative methods and the advanced imaging approaches for an accurate diagnostic work up and the best management of middle ear ailments are presented . As an up-to-date learning resource, based on demonstrated clinico-radiological correlations, this book is a highly valuable teaching tool, especially when contemplating proceeding in middle ear surgery. Middle Ear Diseases is a comprehensive work, aimed for trainees, board candidates and teachers in otolaryngology and otology to respond to every educational need in regard to the most common middle ear pathologies. It is also a useful update for more experienced professionals in this field, as well as radiologists, audiologists and speech therapists.